Composite hydroxide, composite oxide, and method for producing same

By controlling the nucleation and nucleus growth processes of nickel-manganese composite hydroxide, secondary particles composed of multiple primary particles are generated, which solves the problem of secondary particle agglomeration caused by high-temperature calcination and improves the filling property of the positive electrode active material layer and battery performance.

CN120817635APending Publication Date: 2025-10-21PRIME PLANET ENERGY & SOLUTIONS INC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510452775.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-04-15
Filing Date
2025-04-11
Publication Date
2025-10-21

AI Technical Summary

Technical Problem

In the prior art, high-temperature calcination of nickel-cobalt composite hydroxide easily leads to aggregation of secondary particles, resulting in reduced filling capacity of the positive electrode active material layer. A crushing step needs to be added to improve this problem.

Method used

By controlling the pH and ammonium ion concentration in the nucleation and nucleus growth processes, nickel-manganese composite hydroxide is generated in a non-oxidizing environment, forming secondary particles composed of multiple primary particles, inhibiting sintering between secondary particles and avoiding high-temperature calcination treatment.

Benefits of technology

The agglomeration between secondary particles is effectively suppressed, the manufacturing process is simplified, and the filling property of the positive electrode active material layer and the battery performance are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120817635A_ABST
    Figure CN120817635A_ABST
Patent Text Reader

Abstract

This method for producing a composite hydroxide comprises: a nucleation step in which an aqueous solution of ammonia and sodium hydroxide are supplied to an aqueous solution containing a nickel-containing compound and a manganese-containing compound, while maintaining the pH at a liquid temperature of 25 DEG C at 12.0-13.5 and the ammonium ion concentration at 5.3-11.7 g / L; and a nucleus growth step for growing the nucleus while maintaining the pH at a solution temperature of 25 DEG C at 9.7-10.8 and the ammonium ion concentration at 20.0-26.4 g / L.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for producing a composite hydroxide, and further relates to a method for producing a composite hydroxide and a composite oxide, and the composite oxide. Background Art

[0002] Japanese Patent Application Laid-Open No. 2016-210674 describes a nickel-cobalt composite hydroxide and a method for producing the same. Summary of the Invention

[0003] To improve durability due to particle breakage, positive electrode active materials used in non-aqueous electrolyte secondary batteries are sometimes calcined at relatively high temperatures during the manufacturing process of the positive electrode active material to form secondary particles composed of a smaller number of agglomerated primary particles. However, the nickel-cobalt composite hydroxide described in Japanese Patent Application Laid-Open No. 2016-210674, when calcined at relatively high temperatures, often sintered in a state where the secondary particles are aggregated. As a result, the packing capacity of the positive electrode active material layer is sometimes reduced. To improve the packing capacity of the positive electrode active material layer, a crushing step is required during the manufacturing process of the positive electrode active material to break up the agglomerated secondary particles, which increases the number of steps.

[0004] The present invention aims to provide a composite hydroxide containing nickel and manganese as secondary particles formed by agglomeration of a plurality of primary particles, wherein sintering of the secondary particles in an agglomerated state is suppressed, and a method for producing the same, as well as a composite oxide produced using the composite hydroxide and a method for producing the same.

[0005] [1] A method for producing a composite hydroxide containing nickel and manganese, the method comprising:

[0006] a nucleation step of supplying an aqueous solution containing a nickel-containing compound and a manganese-containing compound with an aqueous ammonia solution and sodium hydroxide to generate nuclei while maintaining the pH at a reference temperature of 25° C. between 12.0 and 13.5 and the ammonium ion concentration at 5.3 to 11.7 g / L;

[0007] In the nucleus growth step, the nuclei are grown while maintaining the pH at 9.7 to 10.8 and the ammonium ion concentration at 20.0 to 26.4 g / L based on the liquid temperature of 25°C.

[0008] [2] The method for producing a composite hydroxide according to [1], wherein the composite hydroxide is a compound represented by the following formula (i).

[0009] Ni 1-x-y-z Co x Mn y M z(i)

[0010] (In formula (i),

[0011] 0<x<0.5, 0<y<0.5, 0≤z<0.05,

[0012] M is one or more elements selected from Al, Ti, Zr, B, Mg, Fe, Cu, Zn, Sn, Na, K, Ba, Sr, Ca, W, Mo, Nb, Si, V, Cr and Ge.

[0013] [3] The method for producing a composite hydroxide according to [1] or [2], wherein both the nucleation step and the nucleus growth step are performed under a non-oxidizing environment.

[0014] [4] A method for producing a composite oxide, comprising the method for producing a composite hydroxide according to any one of [1] to [3].

[0015] [5] The method for producing a composite oxide according to [4], which does not include a crushing step.

[0016] [6] A composite hydroxide, which is a secondary particle formed by the aggregation of multiple primary particles.

[0017] The crystallite size Sp in the direction parallel to the (001) plane is 300 nm to 500 nm.

[0018] The crystallite size Sv in the direction perpendicular to the (001) plane is 100nm to 300nm.

[0019] When observed by a scanning electron microscope, the ratio (Lp / Lv) of the length Lp in the direction parallel to the (001) plane of the primary particles to the length Lv in the direction perpendicular to the (001) plane is 10 or more,

[0020] At least a portion of the plurality of primary particles are randomly aggregated.

[0021] The average particle size of the secondary particles is 2.0 to 7.0 μm.

[0022] The above-mentioned composite hydroxide contains nickel and manganese.

[0023] [7] The composite hydroxide according to [6], wherein the BET specific surface area of ​​the secondary particles is 10 m 2 / g or less.

[0024] [8] The composite hydroxide according to [6] or [7], wherein the ratio (I011 / I001) of the intensity I011 of the diffraction peak of the (011) plane of the secondary particles obtained by X-ray diffraction to the intensity I001 of the diffraction peak of the (001) plane is 1.00 or greater.

[0025] [9] A composite oxide comprising a calcined product of a mixture of the composite hydroxide according to any one of [6] to [8] and lithium.

[0026] The foregoing and other objects, features, aspects and advantages of the present invention will become more apparent from the following detailed description of the present invention when taken in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a scanning electron microscope image of the composite hydroxide produced in Example 1.

[0028] Figure 2 This is a diagram for explaining the direction perpendicular to the (001) plane and the direction parallel to the (001) plane of the primary particle.

[0029] Figure 3 This is a scanning electron microscope image of the composite oxide produced in Example 1.

[0030] Figure 4 This is a scanning electron microscope observation image of the composite hydroxide produced in Comparative Example 4.

[0031] Figure 5 This is a scanning electron microscope observation image of the composite hydroxide produced in Comparative Example 4. DETAILED DESCRIPTION

[0032] <Method for producing composite hydroxide>

[0033] The method for producing a composite hydroxide of the present invention comprises the following steps: a nucleation step in which an aqueous solution containing a compound containing Ni and a compound containing Mn (hereinafter also referred to as raw metal hydroxide) is supplied with an aqueous ammonia solution and sodium hydroxide, while generating nuclei while maintaining the pH at 12.0 to 13.5 and the ammonium ion concentration at 5.3 to 11.7 g / L at a liquid temperature of 25°C; and a nucleus growth step in which the nuclei are grown while maintaining the pH at 9.7 to 10.8 and the ammonium concentration at 20.0 to 26.4 g / L.

[0034] The composite hydroxide can be, for example, a precursor of a positive electrode active material used in an active material layer of a positive electrode of a non-aqueous electrolyte secondary battery (hereinafter also referred to as a secondary battery) such as a lithium ion battery. The positive electrode active material can be prepared, for example, by mixing the composite hydroxide with lithium and calcining the mixture. The composite hydroxide can be in the form of particles or can be a secondary particle formed by agglomeration of primary particles.

[0035] The composite hydroxide may further contain, in addition to Ni and Mn, at least one element selected from Co, Al, Ti, Zr, B, Mg, Fe, Cu, Zn, Sn, Na, K, Ba, Sr, Ca, W, Mo, Nb, Si, V, Cr, and Ge (hereinafter referred to as an additive element). The composite hydroxide is preferably a composite hydroxide containing Ni, Mn, and Co (hereinafter also referred to as an NCM composite hydroxide).

[0036] The NCM composite hydroxide may be, for example, a compound represented by the following formula (i).

[0037] Ni 1-x-y-z Co x Mn y M z (i)

[0038] (In formula (i),

[0039] 0<x<0.5, 0<y<0.5, 0≤z<0.05,

[0040] M is one or more elements selected from Al, Ti, Zr, B, Mg, Fe, Cu, Zn, Sn, Na, K, Ba, Sr, Ca, W, Mo, Nb, Si, V, Cr and Ge).

[0041] The composition of the composite hydroxide can be determined by, for example, ICP (inductively coupled plasma) emission analysis.

[0042] (Nucleation process)

[0043] The nucleation step can be performed as follows: for example, the raw metal aqueous solution is added to a reaction tank, and an ammonia aqueous solution and sodium hydroxide are supplied to the reaction tank to maintain the pH and ammonium ion concentration at a liquid temperature of 25°C within a predetermined range while stirring. The raw metal aqueous solution and the ammonia aqueous solution are added to the reaction tank together, and then the ammonia aqueous solution and sodium hydroxide are supplied to the reaction tank to adjust the pH and ammonium ion concentration at a liquid temperature of 25°C.

[0044] The raw metal aqueous solution is prepared by adding a compound containing nickel and a compound containing manganese to water. The compound containing Ni can be, for example, nickel sulfate (NiSO4), nickel nitrate [Ni(NO3)2], nickel carbonate (NiCO3), etc. The compound containing Mn can be manganese sulfate (MnSO4), manganese nitrate [Mn(NO3)2], manganese carbonate (MnCO3), etc. The raw metal aqueous solution can further contain at least one element (hereinafter referred to as an additive element) selected from, for example, Co, Al, Ti, Zr, B, Mg, Fe, Cu, Zn, Sn, Na, K, Ba, Sr, Ca, W, Mo, Nb, Si, V, Cr and Ge. Among them, Co is preferred. The additive element can be added to the raw metal aqueous solution in the form of the element itself or a salt (for example, in the form of sulfate, nitrate or carbonate). When the additive element is Co, the raw metal aqueous solution can include a compound containing Co. The compound containing Co can be, for example, cobalt sulfate (CoSO4), cobalt nitrate [Co(NO3)2], cobalt carbonate (CoCO3), etc.

[0045] The molar ratio of Ni to Mn (Ni:Mn) in the raw metal aqueous solution may be, for example, 1-x:0<x<0.5, 1-x:0.1<x<0.5, or 1-x:0.2<x<0.4.

[0046] When the raw metal aqueous solution contains Co, the molar ratio of Ni, Mn and Co in the raw metal aqueous solution (Ni:Mn:Co) can be, for example, 1-x-y:0<x<0.5:0<y<0.5, or 1-x-y:0.05<x<0.25:0.05<y<0.25 or 1-x-y:0.1<x<0.2:0.1<y<0.2.

[0047] When the raw metal aqueous solution contains Co and other additive elements, the molar ratio of Ni, Mn, Co and other additive elements in the raw metal aqueous solution (Ni:Co:Mn:other additive elements) can be, for example, 1-x-y-z:0<x<0.5:0<y<0.5:0<z<0.05, or 1-x-y-z:0.05<x<0.25:0.05<y<0.25:0.001<z<0.01 or 1-x-y-z:0.1<x<0.2:0.1<y<0.2:0.001<z<0.005.

[0048] The metal content in the raw metal aqueous solution may be, for example, 0.5 to 2.0 mol / L.

[0049] The pH of the ammonia aqueous solution at a liquid temperature of 25°C can be, for example, 11.5 to 13.5. The ammonium ion concentration of the ammonia aqueous solution can be, for example, 5 to 15 g / L. The ammonia aqueous solution can be prepared by adding sodium hydroxide aqueous solution and water to ammonium-containing water (different from ammonia aqueous solution. Hereinafter, also referred to as ammonia water) so that the pH and ammonium ion concentration at a liquid temperature of 25°C are respectively within the above-mentioned ranges. The preparation of the ammonia aqueous solution can be carried out, for example, in a non-oxidizing environment. The preparation of the ammonia aqueous solution can be carried out while heating, for example, at a temperature of 25 to 50°C.

[0050] The nucleation step may be a step of supplying a raw metal aqueous solution and an ammonia aqueous solution to a reaction vessel, stirring while maintaining the pH at a liquid temperature of 25°C between 12.0 and 13.5 and the ammonium ion concentration at a liquid temperature of 5.3 to 11.7 g / L, thereby performing crystallization. Performing the nucleation step while maintaining the pH and ammonium ion concentration at a liquid temperature of 25°C within the above ranges tends to facilitate obtaining a composite hydroxide in which secondary particles are agglomerated and sintering is suppressed.

[0051] In the nucleation step, the raw metal aqueous solution and the ammonia aqueous solution may be supplied to the reaction tank so that the molar ratio of the raw metal aqueous solution to the ammonia aqueous solution is 1:1.

[0052] During stirring, the pH and ammonium ion concentration at a liquid temperature of 25°C can be monitored, and the pH at a liquid temperature of 25°C can be adjusted to the above range by adding sodium hydroxide, and the ammonium ion concentration can be adjusted to the above range by adjusting the concentration of the supplied ammonia solution. The pH can be adjusted by controlling the flow rate of sodium hydroxide using a pH controller.

[0053] In the nucleation step, the solution temperature may be, for example, 10 to 60° C. The nucleation step may be performed for, for example, 1 to 120 minutes. The nucleation step may be performed in a non-oxidizing environment, for example, while nitrogen gas is flowing into the reaction vessel.

[0054] (Core Growth Process)

[0055] The nucleation growth step may be a step of adjusting the solution after the nucleation step in a reaction vessel to a pH of 9.7 to 10.8 and an ammonium ion concentration of 20.0 to 26.4 g / L at a liquid temperature of 25°C, and then stirring the solution after the nucleation step while maintaining the pH of 9.7 to 10.8 and the ammonium ion concentration of 20.0 to 26.4 g / L at a liquid temperature of 25°C, thereby performing crystallization. By performing the nucleation growth step while maintaining the pH and ammonium ion concentration at a liquid temperature of 25°C within the above ranges, there is a tendency to easily obtain a composite hydroxide in which secondary particles are agglomerated and sintering is suppressed.

[0056] In the nucleus growth process, the pH and ammonium ion concentration of the solution at a liquid temperature of 25°C after the nucleation process can be adjusted by simultaneously supplying sodium hydroxide and aqueous ammonia. The pH and ammonium ion concentration of the solution at a liquid temperature of 25°C after the nucleation process can also be adjusted by stopping the supply of the raw metal aqueous solution and aqueous ammonia solution. After the pH and ammonium ion concentration at a liquid temperature of 25°C are adjusted to the above ranges, the raw metal aqueous solution and aqueous ammonia solution are supplied to the reaction tank while maintaining the pH at a liquid temperature of 25°C at 9.7 to 10.8 and the ammonium ion concentration at 20.0 to 26.4 g / L, thereby allowing nuclei to grow. The pH and ammonium ion concentration at a liquid temperature of 25°C can be adjusted in the same manner as in the nucleation process.

[0057] In the nucleation growth step, the solution temperature may be, for example, 10 to 60° C. The nucleation growth step may be performed for, for example, 1 to 24 hours. The nucleation growth step may be performed in a non-oxidizing environment, for example, while nitrogen gas is flowing into the reaction vessel.

[0058] The nucleation step can be terminated by stopping the supply of the raw metal aqueous solution and the ammonia aqueous solution. The solution in the reaction tank is filtered, and the filtrate is washed with water and then dried to obtain a composite hydroxide.

[0059] According to the manufacturing method of the composite hydroxide, a composite hydroxide in which the sintering of secondary particles is suppressed can be obtained in a state where the secondary particles are agglomerated with each other. Therefore, in the manufacturing method of the composite oxide (positive electrode active material) described later, it is easy to carry out a crushing treatment for crushing the agglomerated composite oxide, or there is no need for a crushing step for crushing the composite oxide.

[0060] <Compound Hydroxide>

[0061] The composite hydroxide of the present invention is a secondary particle formed by the aggregation of multiple primary particles, and the crystallite size Sp (hereinafter also referred to as crystallite size Sp) in the direction parallel to the (001) plane is 300nm to 500nm, and the crystallite size Sv (hereinafter also referred to as crystallite size Sv) in the direction perpendicular to the (001) plane is 100nm to 300nm. When observed by a scanning electron microscope (hereinafter also referred to as SEM), the ratio (Lp / Lv) [hereinafter also referred to as ratio (Lp / Lv)] of the length Lp (hereinafter also referred to as length Lp) of the primary particles in the direction parallel to the (001) plane to the length Lv (hereinafter also referred to as length Lv) in the direction perpendicular to the (001) plane is 10 or more. The primary particles are aggregated in a state of random orientation in two directions, namely, the direction parallel to the (001) plane and the direction perpendicular to the (001) plane. Since the composite hydroxide of the present invention has the crystallite sizes Sp and Sv within the above-mentioned ranges, and at least a portion of the multiple primary particles are randomly aggregated, the sintering of the secondary particles in a state of aggregation during the calcination process (hereinafter also referred to as calcination treatment) in the manufacturing process of the positive electrode active material tends to be easily suppressed.

[0062] The composite hydroxide can be produced by the above-mentioned production method. The composite hydroxide is a composite hydroxide containing Ni and Mn, preferably a composite hydroxide containing Ni, Mn, and Co (NCM composite hydroxide), and more preferably a compound represented by the above-mentioned formula (i).

[0063] The crystallite size Sp and crystallite size Sv can be calculated by substituting the half-width of the diffraction peak intensity I001 and I100 of the secondary particles, respectively, obtained by X-ray diffraction (XRD), into the Scherrer equation. By setting the crystallite size Sp and crystallite size Sv within the above ranges, the growth of the primary particles caused by the calcination process is slowed, reducing the contact between the secondary particles due to rapid growth, and thus sintering in a state where the secondary particles are aggregated tends to be easily suppressed. The crystallite size Sp can be, for example, 350 to 450 nm. The crystallite size Sv can be, for example, 150 to 250 nm.

[0064] The ratio (Lp / Lv) can be calculated based on the lengths Lv and Lp of the primary particles measured from an SEM observation image of the surface of the secondary particles. The lengths Lv and Lp can be measured according to the method described in the Examples section below. By setting the ratio (Lp / Lv) within the above range, the growth of the primary particles caused by the calcination process is slowed, and the contact between the secondary particles due to rapid growth is reduced, thereby tending to easily suppress the sintering of the secondary particles in a cohesive state. The ratio (Lp / Lv) can be, for example, 10.3 or more or 10.4 or more.

[0065] Composite hydroxides are secondary particles formed by random aggregation of at least a portion of a plurality of primary particles. Random aggregation refers to a state in which a plurality of primary particles are not regularly arranged in a direction parallel to the (001) plane and are aggregated when the surface of the secondary particle is observed using an SEM. This does not include, for example, a state in which a plurality of primary particles are arranged in a fixed direction parallel to the (001) plane, or a state in which a plurality of primary particles extend radially from the center of the secondary particle in a direction parallel to the (001) plane. Composite hydroxides are preferably secondary particles formed by random aggregation of more than 50% of the plurality of primary particles, more preferably secondary particles formed by random aggregation of more than 70% of the plurality of primary particles, and even more preferably secondary particles formed by random aggregation of all the primary particles.

[0066] The number of primary particles constituting the secondary particles may be plural, for example, 2 or more, 50 or more, 100 or more, 1000 or more, or 10,000 or more, for example, 1,000,000 or less.

[0067] The average particle size of the secondary particles is 2.0 to 7.0 μm. Generally speaking, the secondary particles of composite hydroxides with an average particle size within the above range tend to be easily aggregated and sintered during the calcination process. However, the composite hydroxide of the present invention, despite having an average particle size within the above range, has a tendency for the secondary particles to be difficult to aggregate and sinter during the calcination process. In this specification, the average particle size of the secondary particles can be the particle size D50 at which the cumulative frequency from the smallest particle size in the volume-based particle size distribution is 50%. The volume-based particle size distribution can be measured by a particle size distribution measuring device.

[0068] The BET specific surface area of ​​the secondary particles can be, for example, 10 m 2 / g or less. The BET specific surface area can be measured using a flow-type gas adsorption method specific surface area measuring apparatus. By ensuring that the BET specific surface area of ​​the secondary particles is within the above range, the reactivity with lithium is reduced during the calcination step in the production of the positive electrode active material, and sintering of the secondary particles in a cohesive state tends to be easily suppressed.

[0069] The ratio (I011 / I001) of the intensity I011 of the diffraction peak of the (011) plane of the secondary particles, as determined by XRD, to the intensity I001 of the diffraction peak of the (001) plane can be 1.00 or greater. By setting the ratio (I011 / I001) within the above range, the growth of the primary particles due to the calcination process is slowed, and contact between the secondary particles due to rapid growth is reduced, thereby tending to easily suppress sintering of the secondary particles in a cohesive state. The ratio (I011 / I001) can be, for example, 1.02 or greater, 1.10 or less, or 1.05 or less.

[0070] The composite hydroxide is suitable as a precursor of the positive electrode active material because it easily suppresses sintering of the secondary particles in a cohesive state during the calcination step in the production process of the positive electrode active material. As a result, the filling property of the positive electrode active material in the positive electrode is easily improved.

[0071] <Method for producing composite oxide>

[0072] The method for producing a composite oxide of the present invention includes the method for producing a composite hydroxide described above. The method for producing a composite oxide may further include a mixing step of mixing the composite hydroxide and Li to obtain a mixture, and a calcining step of calcining the mixture.

[0073] In the mixing step, the composite hydroxide and Li can be mixed, for example, so that the ratio of the number of Li atoms in the composite oxide to the total number of metal elements other than Li is 1.0 to 1.3.

[0074] In the calcination step, the mixture may be calcined at a temperature of, for example, 700 to 1000° C. The mixture may be calcined for, for example, 3 to 10 hours. The calcination step may be performed under an oxidizing atmosphere.

[0075] According to the method for manufacturing NCM composite oxides including the method for manufacturing the above-mentioned composite hydroxide, it is easy to obtain a positive electrode active material in which the sintering of secondary particles is suppressed in a state where the secondary particles are agglomerated with each other, so the crushing treatment for crushing the agglomerated composite oxides is easy to carry out, or there is no need for a crushing step for crushing the composite oxides.

[0076] <Compound oxide>

[0077] The composite oxide of the present invention comprises a calcined product of a mixture of the composite hydroxide and lithium. The composite oxide of the present invention can be obtained by the above-mentioned method for producing a composite oxide. The composite oxide may be a composite oxide containing Li, Ni, and Mn, and preferably a composite oxide containing Li, Ni, Mn, and Co.

[0078] The composite oxide may be a secondary particle formed by aggregation of a plurality of primary particles.

[0079] The average particle size of the composite oxide is 2.0 to 7.0 μm.

[0080] The composite oxide may be, for example, a layered metal oxide represented by the following formula (ii):

[0081] Li 1-a1 Ni 1-x-y-z Co x Mn y M z (ii)

[0082] (In formula (ii),

[0083] -0.3<a1<0.3, 0<x<0.5, 0<y<0.5, 0≤z<0.05,

[0084] M is one or more elements selected from Al, Ti, Zr, B, Mg, Fe, Cu, Zn, Sn, Na, K, Ba, Sr, Ca, W, Mo, Nb, Si, V, Cr and Ge).

[0085] Since sintering of the secondary particles in the composite oxide is suppressed when they are aggregated, the packing capacity in the positive electrode is improved, making it suitable as a positive electrode active material for batteries. The proportion of sintered particles in the aggregated state of the composite oxide can be, for example, 14% or less, 7% or less, or 5% or less. If the proportion of sintered particles in the aggregated state of the composite oxide falls within the above range, the packing capacity in the positive electrode active material tends to be improved. The proportion of sintered particles in the aggregated state is measured using the method described in the Examples section below.

[0086] Hereinafter, the present invention will be described in further detail based on examples.

[0087] Example

[0088] [Measurement of average particle size]

[0089] The average particle size of the composite hydroxides produced in Examples and Comparative Examples was measured using a volume cumulative value measured by a commercially available laser diffraction scattering particle size analyzer.

[0090] [Measurement of BET specific surface area]

[0091] The BET specific surface areas of the composite hydroxides prepared in Examples and Comparative Examples were measured using a commercially available flow-type gas adsorption method specific surface area measuring apparatus.

[0092] [Determination of crystallite size and peak intensity ratio]

[0093] The crystallite size Sp in the direction parallel to the (001) plane and the crystallite size Sv in the direction perpendicular to the (001) plane of the composite hydroxides prepared in the Examples and Comparative Examples were measured using a commercially available X-ray diffraction apparatus. In addition, the ratio (I011 / I001) of the peak intensity I011 of the (011) plane to the peak intensity I001 of the (001) plane was calculated.

[0094] [Method for measuring the length of primary particles]

[0095] The composite hydroxides prepared in the examples and comparative examples were observed using a commercially available SEM. Image analysis software was used to extract the primary particles from the measured SEM images, and the length Lp in the direction parallel to the (001) plane and the length Lv in the direction perpendicular to the (001) plane were calculated. Using the calculated lengths, the ratio (Lp / Lv) of the length Lp of the primary particle in the direction parallel to the (001) plane to the length Lv in the direction perpendicular to the (001) plane was calculated. Figure 2 In the figure, the X direction is parallel to the (001) plane, and the Y direction is perpendicular to the (001) plane.

[0096] [Evaluation of the sintering ratio in the cohesive state]

[0097] The composite oxide was cross-sectioned by ion milling. This cross-section was observed using a commercially available SEM to obtain an SEM image. The average particle size of each particle was determined from the obtained image. Particles larger than 8 μm were considered to be particles sintered in a state of agglomeration of multiple particles. The proportion of particles larger than 8 μm among 100 particles was determined as the proportion (%) of particles sintered in agglomerated state after calcination (also referred to as the sintering ratio).

[0098] <Example 1>

[0099] [Production of Composite Hydroxide]

[0100] (Preparation of Aqueous Ammonia Solution)

[0101] Using 28 wt% ammonia water, prepare 2 L of an ammonia solution with an ammonium ion concentration of 11.5 g / L. This 2 L of ammonia solution was added to a 5 L reaction tank. Nitrogen was flowed in to maintain an oxygen concentration of less than 1.0% by volume, and the mixture was stirred at 800 rpm. After the solution in the reaction tank was adjusted to 40°C, an appropriate amount of 30 wt% sodium hydroxide solution was added to adjust the pH to 13.0 at a temperature of 25°C.

[0102] (Preparation of Raw Metal Aqueous Solution)

[0103] Next, nickel sulfate, cobalt sulfate, and manganese sulfate were dissolved in water at a molar ratio of 80:10:10 to prepare a 1.5 mol / L raw metal aqueous solution.

[0104] (Nucleation process)

[0105] The prepared raw metal aqueous solution and ammonia solution are supplied to the reaction tank in a molar ratio of 1:1 at an appropriate time, and the pH at a liquid temperature of 25°C is maintained at 13.0 while stirring, and crystallization is carried out for 60 minutes. The pH at a liquid temperature of 25°C is controlled by adjusting the flow rate of sodium hydroxide using a pH controller. At this time, the concentration of the supplied ammonia solution is adjusted so that the ammonium ion concentration in the reaction solution is maintained at 11.5 g / L. Hereinafter, the pH at a liquid temperature of 25°C in the nucleation process is referred to as the pre-pH. In addition, the ammonium ion concentration in the reaction solution in the nucleation process is referred to as the initial NH3 concentration.

[0106] (Core Growth Process)

[0107] After the nucleation process is completed, sulfuric acid is slowly supplied in such a manner that the pH of the solution in the reaction tank is 10.7 at a liquid temperature of 25°C, and 28wt% ammonia water is supplied at the same time to adjust the ammonium ion concentration in the reaction solution to 21.0g / L. After the adjustment, the supply of liquid to the reaction tank is resumed. At this time, the concentration of the supplied 28wt% ammonia water is adjusted to maintain the ammonium ion concentration in the reaction solution at 21.0g / L. Crystallization is continued for 8 hours while maintaining the pH at a liquid temperature of 25°C (post pH). Then, the supply of solution is stopped to terminate the crystallization, and the resultant is filtered, washed with water, and dried in sequence to obtain the composite hydroxide of Example 1. It should be noted that the environment of the nucleation process and the nuclear growth process is a non-oxidizing environment. Hereinafter, the pH at a liquid temperature of 25°C in the nuclear growth process is referred to as post pH. In addition, the ammonium ion concentration in the reaction solution in the nuclear growth process is referred to as the final NH3 concentration. The SEM observation image of the composite hydroxide of Example 1 is shown in Figure 1 The composite hydroxide of Example 1 is a secondary particle formed by random aggregation of all primary particles.

[0108] [Production of composite oxides]

[0109] The composite hydroxide and the lithium compound were mixed so that the ratio of the number of lithium atoms to the total number of atoms of metal elements other than lithium was 1.10, and the composite oxide of Example 1 was obtained by calcining the mixture at a temperature of 860° C. for 7 hours in an oxidizing atmosphere. The results are shown in Table 1. In addition, the SEM observation image of the composite oxide of Example 1 is shown in Figure 3 .

[0110] <Example 2>

[0111] In (preparation of an ammonia aqueous solution), an ammonia aqueous solution having an ammonium ion concentration of 10.6 g / L and a pH of 13.2 at a liquid temperature of 25°C was prepared. In (preparation of a raw metal aqueous solution), nickel sulfate, cobalt sulfate, manganese sulfate, and zirconium sulfate were dissolved in water at a molar ratio of 69.9:14.9:14.9:0.3 to prepare a 1.6 mol / L raw metal aqueous solution. In (nucleation step), the solution in the reaction tank was maintained at a pH (preliminary pH) of 13.2 at a liquid temperature of 25°C and the ammonium ion concentration was adjusted. The composite hydroxide and composite oxide of Example 2 were produced in the same manner as in Example 1, except that the initial NH3 concentration was maintained at 10.6 g / L while crystallization was carried out, and in the (nucleus growth step), the solution in the reaction tank was adjusted to a pH (final pH) of 10.1 and an ammonium ion concentration (final NH3 concentration) of 24.1 g / L based on a liquid temperature of 25°C, and then crystallization was carried out while maintaining the pH (final pH) at 10.1 and the ammonium ion concentration at 24.1 g / L based on a liquid temperature of 25°C. The results are shown in Table 1.

[0112] Comparative Example 1

[0113] Composite hydroxides and composite oxides were produced in the same manner as in Example 1, except that an ammonia aqueous solution having an ammonium ion concentration of 10.6 g / L and a pH of 11.5 at a liquid temperature of 25°C was prepared in the (preparation of an ammonia aqueous solution), and crystallization was performed while maintaining the pH (preliminary pH) at a liquid temperature of 25°C and the ammonium ion concentration (initial NH3 concentration) at 10.6 g / L in the (nucleation step), and the pH (post pH) at a liquid temperature of 25°C and the ammonium ion concentration (final NH3 concentration) at 21.0 g / L in the (nucleation growth step). The results are shown in Table 1.

[0114] Comparative Example 2

[0115] Composite hydroxides and composite oxides were produced in the same manner as in Example 1, except that an ammonia aqueous solution having an ammonium ion concentration of 10.6 g / L and a pH of 13.0 at a liquid temperature of 25°C was prepared in the (preparation of an ammonia aqueous solution), and crystallization was performed while maintaining the pH (preliminary pH) of the solution in the reaction tank at a liquid temperature of 25°C at 13.0 and the ammonium ion concentration (initial NH3 concentration) at 10.6 g / L in the (nucleation step), and that the solution in the reaction tank was adjusted to a pH (post-pH) of 11.5 at a liquid temperature of 25°C and an ammonium ion concentration (final NH3 concentration) of 21.0 g / L in the (nucleation growth step), and then crystallization was performed while maintaining the pH (post-pH) at a liquid temperature of 25°C at 11.5 and the ammonium ion concentration at 21.0 g / L. The results are shown in Table 1.

[0116] Comparative Example 3

[0117] A composite hydroxide was produced in the same manner as in Example 1, except that an ammonia aqueous solution having an ammonium ion concentration of 10.6 g / L and a pH of 13.0 at a liquid temperature of 25°C was prepared in the (preparation of an ammonia aqueous solution), and crystallization was performed while maintaining the pH (preliminary pH) of the solution in the reaction vessel at a liquid temperature of 25°C at 13.0 and the ammonium ion concentration (initial NH3 concentration) at 10.6 g / L in the (nucleation step), and that the solution in the reaction vessel was adjusted to a pH (post-pH) of 9.3 at a liquid temperature of 25°C and an ammonium ion concentration (final NH3 concentration) of 21.0 g / L in the (nucleation growth step), and then crystallization was performed while maintaining the pH (post-pH) at 9.3 at a liquid temperature of 25°C and the ammonium ion concentration at 21.0 g / L. Crystallization of a composite hydroxide having a uniform particle size and shape could not be achieved.

[0118] Comparative Example 4

[0119] In (preparation of aqueous ammonia solution), an aqueous ammonia solution having an ammonium ion concentration of 9.6 g / L and a pH of 13.3 at a liquid temperature of 25°C was prepared, and in (nucleation process), the solution in the reaction tank was crystallized while maintaining the pH (previous pH) at a liquid temperature of 25°C at 13.3 and the ammonium ion concentration (initial NH3 concentration) at 9.6 g / L, and in (nucleus growth process), the solution in the reaction tank was adjusted to a pH (post-pH) of 10.6 at a liquid temperature of 25°C and an ammonium ion concentration (final NH3 concentration) of 13.3 g / L, and then crystallized while maintaining the pH (post-pH) at a liquid temperature of 25°C at 10.6 and the ammonium ion concentration at 13.3 g / L. Except for this, the same procedure as in Example 1 was carried out to produce composite hydroxides and composite oxides. The results are shown in Table 1. SEM observation images of the composite hydroxides and composite oxides are shown in Table 1, respectively. Figure 4 and Figure 5 .

[0120] <Comparative Example 5>

[0121] Composite hydroxides and composite oxides were produced in the same manner as in Example 1, except that an ammonia aqueous solution having an ammonium ion concentration of 4.7 g / L and a pH of 12.8 at a liquid temperature of 25°C was prepared in the (preparation of an ammonia aqueous solution). In the (nucleation step), crystallization was performed while maintaining the pH (preliminary pH) of the solution in the reaction tank at a liquid temperature of 25°C at 12.8 and the ammonium ion concentration (initial NH3 concentration) at 4.7 g / L. In the (nucleation step), the solution in the reaction tank was adjusted to a pH (post-pH) of 10.8 at a liquid temperature of 25°C and an ammonium ion concentration (final NH3 concentration) of 21.0 g / L, and then crystallization was performed while maintaining the pH (post-pH) at a liquid temperature of 25°C and the ammonium ion concentration (final NH3 concentration) at 21.0 g / L. The results are shown in Table 1.

[0122] <Comparative Example 6>

[0123] Composite hydroxides and composite oxides were produced in the same manner as in Example 1, except that an ammonia aqueous solution having an ammonium ion concentration of 14.2 g / L and a pH of 12.8 at a liquid temperature of 25°C was prepared in the (preparation of an ammonia aqueous solution). In the (nucleation step), crystallization was performed while maintaining the pH (preliminary pH) of the solution in the reaction tank at a liquid temperature of 25°C at 12.8 and the ammonium ion concentration (initial NH3 concentration) at 14.2 g / L. In the (nucleation step), the solution in the reaction tank was adjusted to a pH (post-pH) of 10.6 at a liquid temperature of 25°C and an ammonium ion concentration (final NH3 concentration) of 21.0 g / L, and then crystallization was performed while maintaining the pH (post-pH) at a liquid temperature of 25°C at 10.6 and the ammonium ion concentration (final NH3 concentration) at 21.0 g / L. The results are shown in Table 1.

[0124] <Comparative Example 7>

[0125] A composite hydroxide was produced in the same manner as in Example 1, except that an ammonia aqueous solution having an ammonium ion concentration of 9.6 g / L and a pH of 13.0 at a liquid temperature of 25°C was prepared in the (preparation of an ammonia aqueous solution), and crystallization was performed while maintaining the pH (preliminary pH) at a liquid temperature of 25°C and the ammonium ion concentration (initial NH3 concentration) at 9.6 g / L in the (nucleation step), and that the solution in the reaction tank was adjusted to a pH (post-pH) at a liquid temperature of 25°C and an ammonium ion concentration (final NH3 concentration) of 10.6 and 29.2 g / L in the (nucleation growth step), and then crystallization was performed while maintaining the pH (post-pH) at a liquid temperature of 25°C and the ammonium ion concentration (final NH3 concentration) at 29.2 g / L. The composite hydroxide did not have the target composition.

[0126] <Comparative Example 8>

[0127] In the (preparation of an ammonia aqueous solution), an ammonia aqueous solution having an ammonium ion concentration of 9.5 g / L and a pH of 13.0 at a liquid temperature of 25°C was prepared. In the (nucleation step), crystallization was performed while maintaining the pH (preliminary pH) of the solution in the reaction vessel at a liquid temperature of 25°C at 13.0 and the ammonium ion concentration (initial NH3 concentration) at 9.5 g / L. In the (nucleation growth step), the solution in the reaction vessel was adjusted to a pH (post-pH) of 10.7 at a liquid temperature of 25°C and an ammonium ion concentration (final NH3 concentration) of 21.0 g / L, and crystallization was performed while maintaining the pH (post-pH) at a liquid temperature of 25°C and the ammonium ion concentration (final NH3 concentration) at 21.0 g / L. A composite hydroxide was produced in the same manner as in Example 1 except that the environment in the nucleation step and the nucleation growth step was an oxidizing environment. Crystallization of a composite hydroxide having a uniform particle size and shape could not be achieved.

[0128] [Table 1]

[0129]

[0130] While the embodiments of the present invention have been described, they should be considered in all respects to be illustrative and not restrictive. The scope of the present invention is indicated by the claims, and all modifications within the meaning and scope equivalent to the claims are intended to be included.

Claims

1. A method for producing a composite hydroxide containing nickel and manganese, the method comprising: a nucleation step of supplying an aqueous solution containing a nickel-containing compound and a manganese-containing compound with an aqueous ammonia solution and sodium hydroxide to generate nuclei while maintaining the pH at a reference temperature of 25° C. between 12.0 and 13.5 and the ammonium ion concentration at 5.3 to 11.7 g / L; In the nucleus growth step, the nuclei are grown while maintaining the pH at 9.7 to 10.8 and the ammonium ion concentration at 20.0 to 26.4 g / L based on the liquid temperature of 25°C.

2. The method for producing a composite hydroxide according to claim 1, wherein The composite hydroxide is a compound represented by the following formula (i): Ni 1-x-y-z Co x Mr y M z (i) In formula (i), 0<x<0.5, 0<y<0.5, 0≤z<0.05, M is one or more elements selected from Al, Ti, Zr, B, Mg, Fe, Cu, Zn, Sn, Na, K, Ba, Sr, Ca, W, Mo, Nb, Si, V, Cr and Ge.

3. The method for producing a composite hydroxide according to claim 1 or 2, wherein The nucleation process and the nucleus growth process are both performed in a non-oxidizing environment. 4 . A method for producing a composite oxide, comprising the method for producing a composite hydroxide according to claim 1 .

5. The method for producing a composite oxide according to claim 4, wherein Crushing process is not included.

6. A composite hydroxide, which is a secondary particle formed by the aggregation of multiple primary particles. The crystallite size Sp in the direction parallel to the (001) plane is 300 nm to 500 nm. The crystallite size Sv in the direction perpendicular to the (001) plane is 100nm to 300nm. When observed by a scanning electron microscope, the ratio of the length Lp of the primary particles in the direction parallel to the (001) plane to the length Lv in the direction perpendicular to the (001) plane, i.e., Lp / Lv, is 10 or more. At least a portion of the plurality of primary particles are randomly aggregated, The average particle size of the secondary particles is 2.0 to 7.0 μm. The composite hydroxide contains nickel and manganese.

7. The composite hydroxide according to claim 6, wherein The BET specific surface area of ​​the secondary particles is 10 m 2 / g or less.

8. The composite hydroxide according to claim 6 or 7, wherein The secondary particles have a ratio of the intensity I011 of the diffraction peak of the (011) plane to the intensity I001 of the diffraction peak of the (001) plane determined by X-ray diffraction, that is, I011 / I001, of 1.00 or more. 9 . A composite oxide comprising a calcined product of a mixture of the composite hydroxide according to claim 6 or 7 and lithium.

Citation Information

Patent Citations

  • Nickel cobalt complex hydroxide particles and method for producing the same, positive electrode active material for non-aqueous electrolyte secondary battery and method for producing the same, and non-aqueous electrolyte secondary battery

    JP2016210674A